Structural Changes in N-Glycans on Induced Pluripotent Stem Cells Differentiating Toward Cardiomyocytes. (16th September 2015) - Kawamura, Takuji; Miyagawa, Shigeru; Fukushima, Satsuki; Kashiyama, Noriyuki; Kawamura, Ai; Ito, Emiko; Saito, Atsuhiro; Maeda, Akira; Eguchi, Hiroshi; Toda, Koichi; Miyagawa, Shuji; Okuyama, Hiroomi; et al.
Abstract : N -Glycans were isolated from human induced pluripotent stem cells (iPSCs), iPSC-derived cardiomyocytes (iPSC-CMs), and human cardiomyocytes (hCMCs), and analyzed. The exposed N -acetylglucosamine (GlcNAc) and the nonreduced terminal fucose types of N -glycans decreased, whereas the exposed galactose or the α2-3 NeuAc types increased in the iPSCs during cardiomyogenic differentiation. More bisecting GlcNAc and the triantennary structures were found in the iPSC-CMs than hCMCs or iPSCs, and MGAT3 expression was higher in iPSCs and iPSC-CMs than in hCMCs. Abstract: : Cell-surface glycans vary widely, depending on cell properties. Previously, we reported that the pattern of N -glycan expression on murine induced pluripotent stem cells (iPSCs) changed toward that of the cardiac tissue during cardiomyogenic differentiation. In this study, N -glycans were isolated from human iPSCs, iPSC-derived cardiomyocytes (iPSC-CMs), and human cardiomyocytes (hCMCs). Their structures were analyzed by a mapping technique based on high-performance liquid chromatography elution positions and matrix-assisted laser desorption/ionization time-of-flight mass-spectrometric data. Of 52 isolated N -glycans, the structures of 38 were clearly identified. In addition, 11 structures were partially identified because the binding style and fucose binding site at the nonreduced terminal could not be identified. Quantitation of each type of N -glycan, based on the terminal glycosylation process, revealed that the exposed N -acetylglucosamine (GlcNAc) and the nonreduced terminal fucose types decreased, whereas the exposed galactose or the α2-3 NeuAc types increased in the iPSCs during cardiomyogenic differentiation. However, the bisecting GlcNAc and the triantennary structures were found in relative abundance in the iPSC-CMs in comparison with hCMCs or iPSCs. Expression of MGAT3, a glycosyltransferase-encoding gene that produces the bisecting GlcNAc structures, was higher in iPSCs and iPSC-CMs than in hCMCs. These findings will prove useful in understanding the directional precision of cardiomyogenic differentiation in vitro. Significance: This study focused on N -glycans produced in human induced pluripotent stem cells (iPSCs) and iPSC-derived cardiomyocytes to investigate their change on cardiomyogenic differentiation in vitro. This shows that the expression pattern of N -glycans in human iPSCs changed toward the pattern observed in human cardiomyocytes upon cardiomyogenic differentiation. Structural differences were also observed in the bisecting N -acetylglucosamine and the triantennary structures upon cardiomyogenic differentiation. The findings of this study will help in understanding the directional precision of cardiomyogenic differentiation in vitro.